PENGAWASAN ZONA INTEGRITAS DALAM PELAYANAN PUBLIK DI KABUPATEN SUMEDANG - akadun; Aprilia Fujianti; Ripzki Fauzi; Winda Nurlaena; Yani Ratnasari; Zahra Hennisa Putri (LPPM UNSAP & FISIP UNSAP, 2023)
This research aims to examine the implementation of supervision of integrity zones in public services in Sumedang Regency, management effectiveness, and monitoring strategies applied to improve management effectiveness. The method used in preparing this research report is a qualitative research method with a descriptive type. The sampling technique used was purposive sampling with research informants: Regional Government Affairs Supervisor (PPUPD) Young Expert Inspectorate of Sumedang Regency, Head of Services and Licensing and Public Service Malls Investment Service and One-Stop Integrated Services (MPP) of Sumedang Regency, Division of Licensing and Reporting on National Unity and Politics (KESBANGPOL) of Sumedang Regency, and Radar Sumedang Journalist. Data collection techniques through library research and field studies. Based on the results of the research, it was concluded that the implementation of supervision had been carried out properly. The Sumedang Regency Inspectorate has carried out supervision of the Integrity Zone in accordance with the application of the implementation standards and supervision measurements set by the KemenPan-RB. Observations where there are deviations will be followed up into a draft strategy for evaluation of implementation, and the effectiveness of the implementation of supervision can be measured through output, outcome and impact performance. The success of the implementation of supervision is influenced by the program design that has been determined by the Inspectorate in building the Integrity Zone which is compiled in the Annual Supervision Work Program (PKPT). Factors supporting and inhibiting the implementation of the actor's role in oversight of the Integrity Zone in Public Services are supported by the involvement of ASN through monitoring supervision which is attended by supervisory working groups in each Regional Apparatus Organization and the Regional Apparatus Work Unit concerned.